The Effect of Student's Interpersonal Communication Skills On Student's Learning Outcomes In Mechanical Engineering Subjects - Sukarna, Tasya Fatihah (Universitas Pendidikan Indonesia, 2021)
The differences in student’s background, cognitive, language learning, motor skills, talents and readiness cause the difference of their communication skills. By knowing the different abilities that exist in students, teachers will likely be able to provide learning in the right way. This study was conducted to determine how much the effect of student’s interpersonal communication skills on student’s learning outcomes in Mechanical Engineering subjec. There are 96 samples in this study which also the students of X DPIB 1,2,3 SMK Negeri 2 Garut. The test of student's interpersonal communication skills is a research instrument that author developed, while student’s learning outcomes are seen from the final score of Mechanical Engineering subject on the even semester of 2020/2021 school year. The data analysis technique that used in this study is an aproach of correlation, determination, and simple linear regression analysis. Based on regression analysis, the results showed that there was a positive and significant effect on student’s interpersonal communication skills on student learning outcomes in Mechanical Engineering subject. It means that the better the student’s interpersonal communication skills, also the better their learning outcomes in Mechanical Engineering subjects.